Tuvan national poetry in the 1930s and 1940s - Mizhit, Lyudmila S. (The New Research of Tuva, 2020)
The article examines the first two generations of Tuvan poetry — 1930s and 1940s, with a focus on the texts of collections of poetry published over that time and archival materials preserved at the Tuvan Institute of Humanities and Applied Social and Economic Research.Tuvan poetry was born in the 1930s after the creation of the national writing system and was based on the folk and ethno-cultural traditions of the people, mainly on folk songs. It was also seriously influenced by the Russian and Soviet poetry of that period, especially in composition, creating poetic imagery, complicating poetic thought and providing ideological background. Along with Sergey Pyurbyu and Stepan Saryg-ool, other pioneers who laid the foundation of written Tuvan poetry were Mongush Idam-Syuryun, Baykara Hovenmey, Leonid Chadamba, Salchak Samba-Lyundup, Salchak Tamba, Alexander Tamba-Syuryun, and Vasily Erenchin.In the 1940s Tuvan poetry developed a unique voice of its own, which combined a distinctive ethnic character, a humanist drive towards justice, bright future for all and a new man of a new epoch. The first works of Tuvan literature to reach the status of a classic were S. Pyurbyu’s poem “Chechek” and S. Saryg-Ool’s poem “Sany-Mөge”. They formed the basis of the future lyrical, epic and civil poetics of Tuvan literature.
Keywords: Tuvan People’s Republic; history of Tuva; history of literature; Tuva; Tuvan poetry; Tuvan literature; Tuvan language; yanalif